Changes in Microbiome Dominance Are Associated With Declining Lung Function and Fluctuating Inflammation in People With Cystic Fibrosis - Frey, Dario L.; Bridson, Calum; Dittrich, Susanne; Graeber, Simon Y.; Stahl, Mirjam; Wege, Sabine; Herth, Felix; Sommerburg, Olaf; Schultz, Carsten; Dalpke, Alexander; Mall, Marcus A.; Boutin, Sébastien (Frontiers in Microbiology, 2022)
Airway inflammation and microbiome dysbiosis are hallmarks of cystic fibrosis (CF) lung disease. However, longitudinal studies are needed to decipher which factors contribute to the long-term evolution of these key features of CF. We therefore evaluated the relationship between fluctuation in microbiome and inflammatory parameters in a longitudinal study including a short- (1-year) and a long-term (3+ years) period. We collected 118 sputum samples from 26 CF adult patients and analyzed them by 16S rRNA gene sequencing. We measured the levels of inflammatory cytokines, neutrophil elastase and anti-proteinases; lung function (FEV1 % predicted); and BMI. The longitudinal evolution was analyzed based on i) the rates of changes; ii) the intra-patient stability of the variables; iii) the dependency of the rates of changes on the baseline values. We observed that the diversity of the microbiome was highly variable over a 1-year period, while the inflammatory markers showed a slower evolution, with significant changes only observed in the 3+ year cohort. Further, the degree of fluctuation of the biomass and the dominance of the microbiome were associated with changes in inflammatory markers, especially IL-1β and IL-8. This longitudinal study demonstrates for the first time that the long-term establishment and periodical variation of the abundance of a dominant pathogen is associated with a more severe increase in inflammation. This result indicates that a single time point or 1-year study might fail to reveal the correlation between microbial evolution and clinical degradation in cystic fibrosis.